2017
DOI: 10.1007/s12975-017-0552-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Increased Bradykinin 1 Receptor Contributes to Hemorrhagic Transformation After Ischemic Stroke in Type 1 Diabetic Rats

Abstract: Hemorrhagic transformation (HT) is a major complication of ischemic stroke and further deteriorates neurological outcomes. Bradykinin 1 receptor (B1R) has been proven to mediate vasculo-toxicity in various experimental models. However, its role in the development of HT after stroke remains unclear. We detected the B1R expression in brain tissues with or without HT in a rat model of cerebral ischemia/reperfusion (I/R) with type 1 diabetes, showing higher B1R expression in the hemorrhagic areas than the ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In a preliminary radioligand binding assay, we found that CX807, at a high dose, partially inhibited bradykinin B1 receptor (B1R) binding. It has been shown that B1R antagonist mitigated hemorrhage, improved neurobehavioral deficits, and preserved blood–brain barrier integrity after reperfusion [ 25 ]. CX807 may reduce ICH damage partially through the B1R, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary radioligand binding assay, we found that CX807, at a high dose, partially inhibited bradykinin B1 receptor (B1R) binding. It has been shown that B1R antagonist mitigated hemorrhage, improved neurobehavioral deficits, and preserved blood–brain barrier integrity after reperfusion [ 25 ]. CX807 may reduce ICH damage partially through the B1R, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that some astrocyte-derived factors maintain the BBB function, some astrocyte-derived factors damage the BBB by inducing endothelial cell apoptosis or decreasing the expression of endothelial tight junctionrelated proteins, which include vascular endothelial growth factor (VEGF) [204][205][206][207], glutamate [208][209][210], endothelins (ETs) [21,211,212], MMP [208,213,214], and nitric oxide (NO) [215,216] (Table 1). As zincendopeptidases, MMPs can directly degrade endothelial tight junction-related proteins and ECM molecules, which promotes angiogenesis whereas simultaneously increases BBB permeability [78,217,218]. And it is through the signaling pathway activating or suppressing MMPs that many other factors such as APOE, NO, and ETs get to affect the BBB integrity [201,212,215].…”
Section: The Bbb Integrity-suppressing Effects Of Astrocytesmentioning
confidence: 99%
“…In addition, intravenous injection or overexpression of tissue kallikrein (able to generate kallidin, a bradykinin analog, after cleavage of low-molecular kininogen) has beneficial effects in stroke, which are dependent on B2R activation ( 54 , 55 ). Regarding B1R, the data are more homogenous since most studies described deleterious effects on ischemic lesion size, brain edema and post-stroke inflammation ( 48 , 56 58 ). It is however difficult to isolate the contribution of bradykinin on each of these pathophysiological processes, since reduction of lesion size itself is associated with reduced brain edema and inflammation.…”
Section: Bradykinin Generation As a Unifying Mechanism For The Effectmentioning
confidence: 99%